Nanotechnological basis for advanced sensors - Reithmaier, Johann Peter (NATO science for peace and security series B: physics and biophysics, 2011)
This book is based on the lectures and contributions of the NATO Advanced Study Institute on Nanotechnological Basis for Advanced Sensors held in Sozopol, Bulgaria, 30 May - 11 June, 2010. It gives a broad overview on this topic, and includes articles on: techniques for preparation and characterization of sensor materials; different types of nanoscaled materials for sensor applications, addressing both their structure (nanoparticles, nanocomposites, nanostructured films, etc.) and chemical nature (carbon-based, oxides, glasses, etc.); and on advanced sensors that exploit nanoscience and nanotechnology. In addition, the volume represents an interdisciplinary approach with authors coming from diverse fields such as physics, chemistry, engineering, materials science and biology. A particular strength of the book is its combination of longer papers, introducing the basic knowledge on a certain topic, and brief contributions highlighting special types of sensors and sensor material